Dimensionality reduction by UMAP to visualize physical and genetic interactions - Michael W. Dorrity (Nature Portfolio, 2020)
Dimensionality reduction is often used to visualize expression profiling data in order to find relationships among cells. Here, the authors use Uniform Manifold Approximation and Projection (UMAP) on published expression data of gene deletions of S. cerevisiae to find novel protein interactions.